Pro Single Page Application Development Using Backbone.js and ASP.NET - Fink, Gil; Flatow, Ido; Group, SELA (Apress : Imprint: Apress, 2014)
One of the most important and exciting trends in web development in recent years is the move towards single page applications, or SPAs. Instead of clicking through hyperlinks and waiting for each page to load, the user loads a site once and all the interactivity is handled fluidly by a rich JavaScript front end. If you come from a background in ASP.NET development, you'll be used to handling most interactions on the server side. Pro Single Page Application Development will guide you through your transition to this powerful new application type. The book starts in Part I by laying the groundwork for SPA development. You'll master some JavaScript techniques that will come in useful later on, and get to know the building blocks of a single page application, including modules, routing and MV* frameworks. In Part II, you'll build the client for your application. This is where the magic happens, as the authors take you through the process step by step. Backbone.js is the ideal library for demonstrating SPA development in practice, but you can apply the same principles with other frameworks in your future applications. Part III takes you through the process of building the server side of your application using ASP.NET Web API, and hooking up the two parts of your application to create a working whole. SPA development also comes with its own particular challenges, including tracking history, user interface performance, and how to handle search engine optimization. In the final chapters, the authors guide you through some of these issues and advanced techniques and finish by showing you how to deploy your application. As SPAs become the de facto standard of web application development, the in-depth Pro Single Page Application Development will be your one-stop shop for creating fluid, modern applications on the web.